Implementation Of Center Learning Models At Ra Azzahra Way Jepara East Lampung - Sefri Yanti; Triyana Triyana; Hibana Hibana; Susilo Surahman (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2022)
ABSTRACT . The government's seriousness in improving education is never a joke, this effort is clearly seen in early childhood learning. This research aims to answer the problem that with a small number of centers, teachers should be able to maximize the variety/type of toys, but in reality this has not happened. It also explained about the implementation of learning centers and knowing the factors that support and or hinder the implementation of learning centers at Raudhatul Athfal Azzahra Way Jepara, East Lampung. The design in this study is descriptive. Data collection was carried out using observation and interview techniques. Data analysis using descriptive qualitative techniques. The results of the study: the implementation of learning centers in Raudhatul Athfal Azzahra Way Jepara East Lampung is through five centers, namely the Preparation Center, Art Center, Block Center, Role Playing Center, and Natural Materials Center. Of course there are many inhibiting and supporting factors during this learning change process but reap significant results from the academic abilities and character of the child. Where children are more disciplined, enthusiastic, responsible, and the child's social level increases.Keywords:  Learning Center Model, Early Childhood